Evaluating Epidemiological and Physical Risk Factors in the Development of Chemotherapy-induced Peripheral Neuropathy (CIPN): An In-depth Systematic Review and Meta-analysis - Reeta Khuresha (International Journal of Oncological Nursing and Practices, 2023)
Background of study: Chemotherapy-induced peripheral neuropathy (CIPN) encompasses a range of adverse effects caused by various cytotoxic medications and stands as a primary source of pain among individuals who have survived cancer. In instances of pronounced and sudden CIPN, it might become necessary to diminish chemotherapy dosages or discontinue their application. Currently, no efficacious strategy exists for proactively preventing CIPN, managing established chronic CIPN is constrained, and the risk factors associated with CIPN are also transient and elusive. Objectives of the study: The aim is to identify the epidemiological and physiological risk elements associated with chemotherapy-induced peripheral neuropathy in adults. Research methodology: A systematic review was conducted to locate research articles detailing the risk factors associated with chemotherapy-induced peripheral neuropathy (CIPN). The exploration involved searching through various databases, including Delnet, RemoteXS (PGIMER), Ebsco, Wiley online library, Medline, PubMed, and Web of Knowledge, to find relevant sources. A random-effects meta-regression approach was employed. The quality of the studies was evaluated using the CONSORT and STROBE guidelines, along with adherence to PRISMA guidance. Conclusion and results: This systematic review encompassed 133 research studies, incorporating data from a total of 12,378 patients for the purpose of meta-analysis. A qualitative synthesis was performed to outline factors that were found to influence the risk of chemotherapy-induced peripheral neuropathy (CIPN). Among the 133 studies, 68 of them elucidated distinct risk elements contributing to CIPN. In terms of epidemiological factors, 19 studies highlighted aspects such as age (with a focus on older adults), gender (with females displaying a greater susceptibility to CIPN development), and BMI (with obesity and overweight status being implicated). Physical factors, identified in 17 studies out of the total 133, encompassed characteristics like general weakness, fatigue, elevated distress scores, reduced participation in moderate to vigorous physical activity (MVPA), sleep disturbances, shorter stature, increased body weight, impact on health-related quality of life (HRQOL), and a history of smoking.
Keywords: Chemotherapy-induced peripheral neuropathy (CIPN); Risk factors; epidemiological; meta-analysis; physical; systematic review